2015
DOI: 10.1007/s00256-015-2177-6
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution ultrasound of the posterior femoral cutaneous nerve: visualization and initial experience with patients

Abstract: We confirmed the reliable visualization of the PFCN using HRUS. This offers a new technique for the assessment of the PFCN, which could also be demonstrated with the case series presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 20 publications
0
25
0
1
Order By: Relevance
“…The frequent use of USG for regional anesthesia and pain procedures has familiarized its use among practitioners [1718]. US provides a reliable setup in localizing the anterior fascia of psoas muscle, as well as the relative position of the needle with respect to surrounding tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The frequent use of USG for regional anesthesia and pain procedures has familiarized its use among practitioners [1718]. US provides a reliable setup in localizing the anterior fascia of psoas muscle, as well as the relative position of the needle with respect to surrounding tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Lateral to the hamstring muscle complex tendon, the sciatic nerve, a fascicular and flattened structure, can be easily shown: it descends between and deep to the long head of the biceps femoris and the semimembranosus tendon, superficial to the adductor magnus muscle . A smaller nerve departing from the sciatic nerve, the posterior femoral cutaneous nerve, may be sometimes depicted as well in healthy and slender patients, accompanied by the inferior gluteal artery (Figure ); it distally passes superficial to the long head of the biceps femoris and gradually surfaces up to the cutaneous layer …”
Section: Ultrasound Anatomymentioning
confidence: 97%
“…Hamstring syndrome may be associated with sciatic involvement. Pain with sitting may be also related to posterior femoral cutaneous nerve entrapment because of its closer proximity to the hamstring muscle complex proximal tendons, as this sensory nerve provides the innervation for the inferolateral gluteal region and posterior aspect of the thigh, the superomedial perineal region, and the skin at the popliteal fossa …”
Section: Ultrasound Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Topçu and Aysel reported a single case of an ultrasound (US)‐guided PFCN block for a posterior thigh debridement and skin graft operation in 2014. In 2015, Meng et al reported that the PFCN was readily visualized and blocked with US guidance in the distal and mid thigh, but with some difficulty in the proximal thigh. However, a more proximal approach would be desirable for providing complete anesthesia to the posterior thigh.…”
mentioning
confidence: 99%